KEEFEKTIFAN KETERAMPILAN MEMBACA SISWA SEKOLAH DASAR MELALUI MODEL PROBLEM BASED LEARNING BERBANTU MEDIA KARTU BACA - Ariyani, Ratna; Wijayanti, Arfilia; Putriyanti, Lina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of the Problem Based Learning (PBL) model assisted by reading card media in improving the reading skills of lower-grade elementary school students. The research applied a quantitative experimental approach with a one group pretest-posttest design. The subjects were 21 first-grade students from SD Negeri 3 Sengonwetan, Grobogan Regency. Data collection techniques included pretests and posttests to measure students' initial and final reading abilities, as well as observations, interviews, and documentation for in-depth supporting data.The results indicated a significant improvement in students’ reading abilities. The average pretest score was 79.76, which increased to 95.24 in the posttest. Statistical t-test analysis showed a significance value of 0.004 (< 0.05) with a t-count of 3.281 > t-table 1.725, indicating a significant difference between pretest and posttest scores and acceptance of the alternative hypothesis (Ha). Additionally, assessment results in letter reading, word reading, and syllable reading revealed that most students achieved perfect scores, demonstrating mastery of basic reading skills (BRS).Observational and interview data further confirmed that using reading card media within the PBL framework enhanced students’ learning motivation, self-confidence, and active participation. Students showed greater enthusiasm in reading activities and were able to complete reading tasks independently and in groups.In conclusion, the PBL model integrated with reading card media is proven to be an effective instructional strategy for significantly improving elementary students' reading skills, both in cognitive and affective aspects.